Lung stereotactic ablative body radiotherapy: A large scale multi-institutional planning comparison for interpreting results of multi-institutional studies. Issue 4 (April 2016) - Giglioli, Francesca Romana; Strigari, Lidia; Ragona, Riccardo; Borzì, Giuseppina R.; Cagni, Elisabetta; Carbonini, Claudia; Clemente, Stefania; Consorti, Rita; El Gawhary, Randa; Esposito, Marco; Falco, Maria Daniela; Fedele, David; et al.
Highlights: To compare from dosimetric and equivalent doses point of view, SABR plans of lung cancer patients from 26 centers. To compare plans with various TPS's, delivery technologies and dose normalization approaches. To analyze the gEUD2, MLD2 and constraints fulfillment against planner expertise and involved technology. Abstract: Purpose: A large-scale multi-institutional planning comparison on lung cancer SABR is presented with the aim of investigating possible criticism in carrying out retrospective multicentre data analysis from a dosimetric perspective. Methods: Five CT series were sent to the participants. The dose prescription to PTV was 54 Gy in 3 fractions of 18 Gy. The plans were compared in terms of PTV-gEUD2 (generalized Equivalent Uniform Dose equivalent to 2 Gy), mean dose to PTV, Homogeneity Index (PTV-HI), Conformity Index (PTV-CI) and Gradient Index (PTV-GI). We calculated the maximum dose for each OAR (organ at risk) considered as well as the MLD2 (mean lung dose equivalent to 2 Gy). The data were stratified according to expertise and technology. Results: Twenty-six centers equipped with Linacs, 3DCRT (4% – 1 center), static IMRT (8% – 2 centers), VMAT (76% – 20 centers), CyberKnife (4% – 1 center), and Tomotherapy (8% – 2 centers) collaborated. Significant PTV-gEUD2 differences were observed (range: 105–161 Gy); mean-PTV dose, PTV-HI, PTV-CI, and PTV-GI were, respectively, 56.8 ± 3.4 Gy, 14.2 ± 10.1%, 0.70 ± 0.15, and 4.9 ± 1.9. Significant correlations for PTV-gEUD2 versus PTV-HI, and MLD2 versus PTV-GI, were observed. Conclusions: The differences in terms of PTV-gEUD2 may suggest the inclusion of PTV-gEUD2 calculation for retrospective data inter-comparison.